Arab Economic Integration: Missing Links - Hoekman, Bernard (2012)
This paper surveys the recent literature on Arab economic integration and discusses the goals and progress that has been made to date and some of the key policy, regulatory, and political factors that underpin the segmentation of Arab markets. It argues that there has been an excessive focus by both analysts and policy makers on trade in goods and that the prospects for--and returns to--efforts to deepen integration of other markets (services, labour, and capital) are likely to be higher.